Electronic Government 13th IFIP WG 8.5 International Conference, EGOV 2014, Dublin, Ireland, September 1-3, 2014, Proceedings - Janssen, Marijn; Scholl, Hans Jochen; Wimmer, Maria A.; Bannister, Frank Edward; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 13th IFIP WG 8.5 International Conference on Electronic Government, EGOV 2014, held in Dublin, Ireland, in September 2014. The 26 revised full papers presented were carefully reviewed and selected from 70 submissions. The papers have been organized in the following topical sections: foundations; services and interoperability; policy and stakeholders; open data; and design and values.
The EGOV Research Community: An Update on Where We Stand -- The Development in Leading e-Government Articles 2001-2010: Definitions, Perspectives, Scope, Research Philosophies, Methods and Recommendations - An Update of Heeks and Bailur -- An Online Transparency for Accountability Maturity Model -- Towards an Evaluation Model for Open Government: A Preliminary Proposal -- Contextual Factors Influencing Health Information Systems Implementation in Public Sector – Investigating the Explanatory Power of Critical Success Factors -- PA Meets IS Research: Analysing Failure of Intergovernmental Information Systems via IS Adoption and Success Models -- Interconnecting Governments, Businesses and Citizens – A Comparison of Two Digital Infrastructures -- The Role of Trust in the Prioritization of Channel Choices -- Identifying a Public Sector Information Systems (PSIS) for E-service: A Case of Land Records E-service in Bangladesh -- Source and Channel Choices in Business-to-Government Service Interactions: A Vignette Study -- Connecting People: Semantic-Conceptual Modeling for Laws and Regulations -- Modelling Process Intensive Scenarios for the Smart City -- Shared Services: Maverick or Originator? -- Assessing Policy Making for ICT Innovation: A Decision Support Research Agenda -- Open Government Data: Facilitating and Motivating Factors for Coping with Potential Barriers in the Brazilian Context -- Analyzing Stakeholders in Complex E-Government Projects: Towards a Stakeholder Interaction Model -- LAN House* Implementation and Sustainability in Brazil: An Actor-Network Theory Perspective -- Bridging the Digital Divide at the Regional Level? The Effect of Regional and National Policies on Broadband Access in Europe’s Regions -- Designing a Second Generation of Open Data Platforms: Integrating Open Data and Social Media -- Categorization of Brazilian Internet Users and Its Impacts on the Use of Electronic Government Services -- A Decision Model for Data Sharing -- Policy, Process, People and Public Data -- Is the Public Motivated to Engage in Open Data Innovation? -- Dialectics and Contradictions in Public Procurement of Information Systems -- Strategic Aspects for Successful E-government Systems Design: Insights from a Survey in Germany -- Proposing an Entrepreneurial Process for the Co-creation of IT Value -- Developing Value-Centric Business Models for Mobile Government.
Keywords: Computers and civilization; Computers; Law and legislation; Application software; Computers and Society; Legal Aspects of Computing; Information Systems and Communication Service; Computer Appl. in Administrative Data Processing